2016
DOI: 10.5863/1551-6776-21.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Communication Strategies for Empowering and Protecting Children

Abstract: Communication with children and adolescents is an area that requires special attention. It is our job as health care professionals to ensure that the information being relayed is provided at a level that can be understood, to ensure patient safety as well as keep a child or adolescent engaged in their own medical care and decision making. This article discusses the importance of communication with children, adolescents, and their caregivers. It focuses on the overall importance of health literacy in communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…There is a plethora of evidence suggesting that effective communication with HIV seropositive children can marginally improve their treatment adherence, reduce adverse events, and reduce stress and anxiety [1, 16, 18, 26, 32]. Moreover, communicating health messages to HIV seropositive children has proved to be effective in improving their psychological and behavioural outcomes and in some instances, it has been proved to promote self-care [33]. In addition, effective communication between HCWs, PCGs, and children creates an enabling environment for early HIV seropositive status disclosure to children to prevent inadvertent transmission of the virus later in life when they become sexually active and it also improves medication adherence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a plethora of evidence suggesting that effective communication with HIV seropositive children can marginally improve their treatment adherence, reduce adverse events, and reduce stress and anxiety [1, 16, 18, 26, 32]. Moreover, communicating health messages to HIV seropositive children has proved to be effective in improving their psychological and behavioural outcomes and in some instances, it has been proved to promote self-care [33]. In addition, effective communication between HCWs, PCGs, and children creates an enabling environment for early HIV seropositive status disclosure to children to prevent inadvertent transmission of the virus later in life when they become sexually active and it also improves medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that children need the support, and participation of PCGs in their healthcare experience [18, 19, 33, 38]. HCWs are therefore obligated to furnish PCGs with the relevant information regarding their child's illness, so that they can provide the necessary support to their child [5].…”
Section: Resultsmentioning
confidence: 99%
“…A significant number of skills are required in approaching and communicating with younger children, taking into account the patient's developmental stage. 17,18 Furthermore, it is interesting to note that between these two groups, there was no significant difference in self-reported confidence scores on any of the ten questions after pediatric placement. This indicates that the medical curriculum and course structure have successfully brought students to a standardized level of self-perceived confidence, regardless of experience.…”
Section: Discussionmentioning
confidence: 96%
“…In comparison with Al‐Mosaiwi and Johnstone's () study, the current sample used fewer absolutist words. Greater flexibility and less rigidity in thinking styles might be expected in adolescence compared with adulthood due to brain plasticity peaking at this developmental stage (Dahl, ; Tamnes et al, ), and this cognitive process might explain differences in communication patterns (Bell & Condren, ; Chomsky, ). Further linguistic analyses in adolescent and chronic illness populations may be needed to inform a future iteration of a coding scheme.…”
Section: Discussionmentioning
confidence: 99%